E-016 Angioplasty following pipeline embolization device delivery safely improves the midterm angiographic outcome. (22nd July 2018) - Caroff, J; de Macedo Rodrigues, K; Howk, M; Rex, D; Massari, F; Kühn, A; Wakhloo, A; King, R; Gounis, M; Puri, A
Abstract : Introduction: Pipeline Embolization Device (PED) has proven to be an effective treatment for intracranial aneurysm with high rates of long-term complete occlusion. 1, 2 However, some aneurysms either do not achieve complete occlusion 3–6 or heal in a delayed fashion 7 during which the aneurysm is not protected from rupture. Recent scientific reports from animal models show that poor wall apposition of PED devices can lead to delayed occlusion of aneurysms. 8, 9 The purpose of this study was to compare the mid-term occlusion rates with or without balloon angioplasty (BA) after PED delivery. Materials and methods: From October 2011 to September 2016 all consecutive patients treated with a PED and with an available angiographic follow-up performed between 6 and 24 months were included in this study. BA was performed at the operator's discretion based on imaging findings. Aneurysms with previous history of stenting or cases where a non flow-diverter stent was associated with the PED were excluded from analysis. Clinical presentations, technical details, intra- and perioperative complications, and clinical and angiographic outcomes were recorded in a prospectively maintained database. Results: 158 aneurysms were included and angioplasty was performed in 49% of cases. Average follow-up interval was 12 months for both groups (p=0.6). Patients' demographics and aneurysm characteristics were not different between the two groups (table 1). The number of PED per case was slightly greater in the control group. Complete occlusion rate was significantly higher in the angioplasty group (88%) than in the control group (73%); p=0.017. No BA related hemorrhagic complication was reported. Angioplasty was not associated with a more frequent use of anti GPIIb/IIIa inhibitors (p=0.2), a marker of intra-operative thrombotic event. No increase in baseline mRS score was found during follow-up in the BA group. Conclusions: Balloon angioplasty appears to be a safe technique to improve the midterm angiographic outcome after Pipeline Embolization Device treatment. References: Becske, et al. Neurosurgery 2017. Brinjikji, et al. Stroke 2013. Shapiro, et al. Journal of Neurosurgery 2016. Brasiliense, et al. WNEU 2017. Adeeb, et al. AJNR 2017. Gressot, et al. WNEU 2016. Walcott, et al. JAMA Neurol 2016. King, et al. JNIS 2017. Rouchaud al. AJNR 2016. Disclosures: J. Caroff: None. K. de Macedo Rodrigues: None. M. Howk: None. D. Rex: None. F. Massari: None. A. Kühn: None. A. Wakhloo: 1; C; Philips Med (research and equipment support and MAB); Medtronic Consultant: Stryker Neurovascular. 2; C; Stryker Neurovascular. 3; C; Harvard Postgraduate Course; Baptist Health, Jacksonville, FL. 4; C; EpiEP; Neural Analytics; 4L Analytics; InNeuroCo. 5; C; Co-founder, CMO and Board member InNeuroCo. R. King: None. M. Gounis: 1; C; Medtronic Neurovascular, Stryker Neurovascular, Cerenovus Neurovascular. 2; C; Cerenovus Neurovascular, Medtronic Neurovascular, Phenox, Stryker Neurovascular. A. Puri: 1; C; Medtronic Neurovascular, Stryker Neurovascular. 2; C; Cerenovus Neurovascular, Medtronic Neurovascular, Stryker Neurovascular.